Metacognition Strategies And Their Relationship To Self-efficacy Among Third Year Secondary Students - Babouhoun Khaled; Tabli Mohamed Taher (University of Eloued جامعة الوادي, 2024)
Abstract: This research paper aimed to verify the existence of a correlation between metacognitive strategies and self-efficacy among third-year secondary students, and proceeded from the following hypotheses: 1) the degree of use of metacognitive strategies by third-year secondary students is high, 2) the degree of self-efficacy among secondary school students The third year of secondary school is high, 3) There is a correlation between metacognitive strategies and self-efficacy among third year secondary school students. The descriptive correlative approach was adopted and applied to a simple random sample of 150 students from the third year of secondary school in the state of Ghardaia . The two measures (metacognitive strategies and self-efficacy) were used. The study reached a number of results that emphasize the importance of students' use of metacognitive strategies in their knowledge life and personal affairs, the high self-efficacy they have, and the existence of a statistically significant correlation between metacognitive strategies and self-efficacy among third-year secondary school students.
Keywords: Metacognition strategies; Self-efficacy; Third year secondary students